"Haeckelite", a new low dimensional cousin of boron nitride for biosensing with ultra-fast recovery time: a first principles investigation. Issue 42 (11th October 2018) - Roondhe, Basant; Jha, Prafulla K.
Abstract : The study suggests that a new Haeckelite structure of boron nitride may act as an excellent material with ultrafast recovery time for sensing and DNA sequencing applications in future. Abstract : We performed state-of-the-art first principles calculations under the framework of dispersion corrected density functional theory to investigate the electronic and vibrational properties of a recently found allotrope of BN, with octagonal and square ring forming planar haeckelite structures (haeck-BN). We further investigated the adsorption mechanism of five nucleobases adenine (A), guanine (G), cytosine (C), thymine (T) and uracil (U) over haeck-BN to explore its applicability in biosensing. The dispersion correction (DFT-D2) is included to appropriately consider van der Waals interactions. The order of adsorption energy of nucleobases over haeck-BN has the following order: G > T > A ≈ C > U. Significant variation in electronic properties, density of states and work function confirm the adsorption of nucleobases. To check the reusability of haeck-BN as a biosensor toward nucleobases, we calculated the recovery time. Ultrafast recovery times (in millisecond) of 292 ms, 130 ms, 120 ms, 160 ms and 0.6 ms were predicted for G, A, C, T and U, respectively. Our finding suggests that haeck-BN can be utilized as a biosensor for the detection of nucleobases due to its superiority to graphene, h-BN and boron nitride nanotubes, and can be further explored for photocatalysis.